3D Pore-network quantitative analysis in deformed carbonate grainstones. (April 2017) - Zambrano, Miller; Tondi, Emanuele; Mancini, Lucia; Arzilli, Fabio; Lanzafame, Gabriele; Materazzi, Marco; Torrieri, Stefano
Abstract: This study consists of a three-dimensional (3D) assessment of the pore network properties (i.e., porosity, pore connectivity, specific surface area) in deformed carbonate grainstones cropping out in Sicily and Abruzzo regions (Italy). Previous studies, including microphotography, mercury injection analysis, and in-situ air permeameter measurements, have reported permeability differences (in the range of two-to-three orders of magnitude) between the carbonate grainstones exposed in Sicily and Abruzzo, that cannot be explained by only considering the differences of porosity. In this study, the pore network properties of suitable rock samples were studied by quantitative analysis of X-ray micro-CT images using both synchrotron and microfocus sources. On the basis of the results, inferences about the control of pore network properties on permeability were made for both host rock and deformation bands. In the host rocks, high values of connectivity seem to be associated with high values of permeability, whereas higher values of the specific surface area seem to correspond to lower permeability. Within the deformation bands (DBs), both porosity and pore connectivity are reduced except for local solution-enlarged stylolites and fractures (slip surfaces) preferentially connected parallel to the DB. Highlights: Pore properties of the studied rocks may explain variability on their permeability. In deformation bands, connected porosity is reduced by cementation and cataclasis. The Zone III is characterized by zero connected porosity, which may buffer fluid flow. In fault cores, connected pores are likely solution-enlarged stylolites and fractures.